Avoiding uncertain buying intentions: Does WebQual matter? - Nawras M. Nusairat; Khalid N. AlZubi; Lama Abubaker; Hadeel Abdellatif; Abdel Hakim O. Akhorshaideh; We’am Aref Alkhalayleh; Jassim Ahmad Al-Gasawneh (International Journal of Data and Network Science, 2023)
The purpose of this research is to examine the effect of Web Quality (WebQual) on travelers’ online behavioral intentions through examining the mediating role of travelers’ perceived trust in the context of travel agencies in Jordan. Based on the extant literature, a conceptual model was developed. Data was collected through a questionnaire survey which was administered to a convenient sample of 300 participants. Structural equation modeling SEM with smart PLS 3 was implemented as an analytical methodology to process data. The results suggest that WebQual factors are significant in predicting travelers’ behavioral intentions. Moreover, the results demonstrate that perceived trust has a significant impact on travelers’ behavioral intentions and a partial mediation was also found for travelers’ perceived trust on the relationship between WebQual and travelers’ behavioral intentions. Discussion, conclusions, research limitations and areas for future research are all provided.